Strengthening Wasatiyyah for the Youth through Islamic Education - Azhari Andi; Muhammad Nasir; Eya Benlakhdhar; Shana Jasmin (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2023)
This paper aims to discuss strengthening wasatiyyah among the youth in Indonesia. This issue is critical since the development of radicalism among youth has been increasing. The data will be analyzed through a descriptive-analytic approach. The analysis finds that pesantren and Islamic schools have play important role in strengthening wasatiyyahamong Indonesian youth through implementing the value of multicultural education that emphasizes moderation for the youth. It is no wonder since multicultural education is the priority value that must be included in every learning in pesantren and Islamic schools as a mandate from the Ministry of the Religion of the Republic of Indonesia. Besides, the principles of pesantren and Islamic schools have a significant impact on fostering a moderate attitude towards the youth.